(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Lung cancer is one of the major causes of cancer related death worldwide, while non-small cell lung cancer (NSCLC) consists of 85% of all lung cancer cases. Despite adequate treatment, most of the NSCLC patients progress to advance stages. Single or doublet-chemotherapy are considered as standard care for advance NSCLC patients. Gefitinib is considered as standard therapy for EGFR mutant advanced NSCLC. Recently, a human monoclonal antibody called Nivolumab has shown encouraging efficacy for advanced NSCLC patients. The aim of this systematic review is to show the efficacy of nivolumab in comparison to single or doublet chemotherapy and gefitinib. Method: A systematic search was performed in PubMed, Google Scholar and Cochrane Library to identify primary research, published in English language between 2000 and 2018, involving Nivolumab, chemotherapy and gefitinib for advanced NSCLC patients. The primary outcome of interest was median overall survival (mOS). The secondary outcome of interest were progression free survival, objective response rate and grade-3 and treatment related adverse effects. Results: After screening 600 full-text articles, 17 clinical studies involving 9284 patients of advanced NSCLC were included. All treatment regimen seemed to be feasible. The mOS for nivolumab was ranging between 9.2 months and 16.2 months; for chemotherapy between 6 months and 18.8 months; and for gefitinib between 7.6 months and 30.5 months. Conclusion: Nivolumab is more effective and safe for EGFR non-mutant advanced NSCLC patients than either chemotherapy or gefitinib. However, gefitinib is more effective than nivolumab for EGFR-mutant NSCLC patients. J Bangladesh Coll Phys Surg 2024; 42: 176-188